2007
DOI: 10.1080/02673030701254103
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital, Neighbourhood Attachment and Participation in Distressed Urban Areas. A Case Study in The Hague and Utrecht, the Netherlands

Abstract: and-conditions-of-access.pdf This article may be used for research, teaching and private study purposes. Any substantial or systematic reproduction, redistribution , reselling , loan or sub-licensing, systematic supply or distribution in any form to anyone is expressly forbidden. The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy of any instructions, formulae and drug doses should be independently ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 50 publications
(60 reference statements)
5
76
0
2
Order By: Relevance
“…In the existing literature, one of the most consistent positive socio-demographic predictor of place attachment and social interaction is length of residence [6,8], and of community participation is education level [11,59]. Nevertheless, not all studies have found a significant relationship between these predictors and their respective place relationship dimensions [1,6,60]. Researchers have suggested that the erratic patterns of relationships between these socio-demographic variables and place relationship dimensions may be due to extraneous physical or social environmental factors [1,6,61].…”
Section: Multiple Regression Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…In the existing literature, one of the most consistent positive socio-demographic predictor of place attachment and social interaction is length of residence [6,8], and of community participation is education level [11,59]. Nevertheless, not all studies have found a significant relationship between these predictors and their respective place relationship dimensions [1,6,60]. Researchers have suggested that the erratic patterns of relationships between these socio-demographic variables and place relationship dimensions may be due to extraneous physical or social environmental factors [1,6,61].…”
Section: Multiple Regression Analysismentioning
confidence: 99%
“…Nevertheless, not all studies have found a significant relationship between these predictors and their respective place relationship dimensions [1,6,60]. Researchers have suggested that the erratic patterns of relationships between these socio-demographic variables and place relationship dimensions may be due to extraneous physical or social environmental factors [1,6,61]. Table 5.…”
Section: Multiple Regression Analysismentioning
confidence: 99%
See 3 more Smart Citations